Effect of temperature on the electrical conductivity of polyaniline/cashew gum blends - Amorim, Daniel R.B.; da Silva Guimarães, Iran; Fugikawa-Santos, Lucas [UNESP]; Vega, Maria L.; da Cunha, Helder N. (Elsevier, 2020)
The electrical properties of polymeric films/blends comprising polyaniline (PANI) and cashew gum (CG) blends were studied by impedance spectroscopy in the temperature range from 300 K to 353 K. Protonation promoted by sulfuric acid was responsible for changing the oxidation state from undoped emeraldine base (EB) to doped emeraldine salt (ES). The low-frequency conductivity of the films varied more than 6 orders of magnitude by doping. In (PANI- EB)/CG blends, the presence of cashew gum acts a dispersing agent, lowering the electrical conductivity contrasting to (PANI-ES)/CG blends, where the electrical conductivity increases with CG concentration up to 20% (w/w). Moreover, undoped films presented a thermally-activated electrical conductivity, whereas doped films presented a decrease in the conductivity by increasing temperature. An equivalent circuit model is proposed to analyze the data by considering the system being composed of highly conductive regions separated by insulating/semiconducting ones.
Keywords: Cashew gum; Conductivity; Polyaniline; Thermal effect